PENGARUH PEMBERIAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KARYAWAN TETAP PT. LG ELECTRONICS INDONESIA KANTOR CABANG PEKANBARU - Lensi Gusti Prapti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of motivation and discipline of work on employee performance on permanent employees of PT. LG Electronics Indonesia Branch Office Pekanbaru partially and simultaneously. This study used questionnaires as a data gathering tool distributed to 37 employees at PT. LG Electronics Indonesia Branch Office Pekanbaru. The data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 17.0 by performing validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis (R²) and hypothesis test with t test (partial) and F ( Simultaneous).The results showed that the results of the first variable hypothesis testing is the provision of motivation to employee performance is t_Hitung (4.847)> t_Table (2.030), meaning that the variable of motivation has a significant effect on employee performance. The second variable of work discipline on employee performance is t? (3.553)> t_Table (2.030), work discipline variable significantly influence employee performance. Result of F test giving motivation and work discipline that is F arithmetic (20,145)> F table (3,28), meaning giving motivation and work discipline simultant influence significantly to employee performance.Keywords: Giving Motivation, Work Discipline, Employee Performance1) Student of faculty social sciences and political science, University Of Riau2) Supervisor Lecture of faculty social sciences and political science, University Of Riau.